Olympiads in informatics: problems from the mathematical approach - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2004)
The paper deals with the problems delivered at the National Olympiads in Informatics from the mathematical approach. Over 300 of problems have been analyzed, they were classified, and statistical analysis of each group was submitted. It was found that in Lithuanian Olympiads in Informatics the problems bound with graphs dominates. These problems usually are solved implementing different kind of methods.
Keywords: algorithmical problems; programming teaching; olympiads in informatics